Web-based biology e-module to improve scientific literacy and collaboration through Surili biodiversity context - Pradiana, Maulani; Hindriana, Anna Fitri; Yadi Ismail, Agus (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Scientific literacy and collaborative learning remain major challenges in biology education, particularly in ecosystem topics that often lack of meaningful contextualization. This study aimed to develop and evaluate a web-based biology e-module integrated with a WhatsApp chatbot and the Surili (Presbytis comata) biodiversity context to improve students’ scientific literacy and collaboration skills. The study employed a research and development (R&D) approach using the ADDIE model combined with a quasi-experimental design. A total of 67 tenth-grade students from MAN 3 Cirebon participated, involving an experimental class (N = 32) and a control class (N = 35). Product feasibility was assessed through expert validation, while effectiveness was evaluated using scientific literacy tests, collaboration observations, and student response questionnaires. The e-module achieved a very feasible category with an average expert validation score of 95%. The experimental group demonstrated significantly higher scientific literacy (ANCOVA, p < 0.001), with a higher N-Gain (0.705) than the control group (0.396). Collaboration skills also improved significantly (Mann–Whitney, p < 0.001). Students reported highly positive responses (85.05%). These findings suggest that integrating a WhatsApp chatbot, web-based e-module, and local biodiversity context effectively enhances scientific literacy and collaboration in biology education.